Web-Based Sales Information System by Implementing Customer Relationship Management (CRM) - Oqi Dyah Larasakti; Emilya Ully Artha; M Maimunah (Prosiding University Research Colloquium, 2022)
Anna Snack Wiran is one of the businesses engaged in the food sector which is located in Rambeanak 2 Village, Mungkid, Kab. Magelang. Anna Snack Wiran sells various types of ancient snacks, then accepts individual and wholesale food orders by visiting the store or online. Anna Snack Wiran already has her own label and has a PIRT number that has passed the test from the Magelang District Health Office. Anna Snack Wiran, frequent errors in managing and storing product data, sales data, customer data and customers must come to the store. Customers often find it difficult to get information about products such as product name, product type, product price, and product stock availability. Therefore, the solution in maintaining service to customers, especially those outside the city, is the application of the concept of customer relationship management or Customer Relationship Management (CRM). That is, a business strategy to select and manage the most profitable customer relationships, CRM requires a customer-centered business philosophy and culture to support effective marketing, sales and service processes, enabling management. or setting up good relations with customers. In this research, it can make it easier for customers to get product information, can make it easier for owners or admins to manage data so that the data storage process can be more accurate and stored neatly, and the application of CRM so as to create customer loyalty that is maintained for good customer relationships. sustainable with the criteria of customers buying very often and rarely buying. This is evidenced by the large percentage of blackbox testing that gets 100% accurate, in accuracy of calculations it also gets a value of 100% and testing the customer satisfaction system with a Likert scale gets 88.218% very satisfying.